Lagu Marsinondang Dibaen Jesus Karya Philip Paul Bliss: Analisis Bentuk dan Makna Lagu - Emmi Simangunsong; Ance Juliet Panggabean; Ronald Heriko Saragih; Eston Hernandes P. (Grenek: Jurnal Seni Musik, 2025)
This study aims to analyze the form and meaning of the song Marsinondang Dibaen Jesus from the Ende HKBP book number 518 by Philip Paul Bliss. The song is sung by the congregation during Sunday services at the HKBP Church and other services. The song was composed by Philip after hearing a sermon from Dwight Lyman Moody about a storm that occurred at the Cleveland harbor docks which had two lighthouses, called the upper light and the lower light. The captain couldn't see the lower lights, which caused the ship to sink to the bottom of the sea. Only a small number of the crew survived, and most drowned. Based on Moody's account, Philip wrote the song "Let the Lower Lights be Burning." The song was then translated by missionaries into the Toba Batak language based on the meaning of the song and gave the song the title Marsinondang Dibaen Jesus (“shining because of Jesus”). This research used a descriptive qualitative method. The results showed that the song's form is binary (A, B) and has eight melodic motifs. The meaning contained in the song "Marsinondang Dibaen Jesus" states that God's faithful love must continue to be reflected in life, God's faithful love must continue to be expressed so that others can be saved and find the path to truth. The meaning of this song is emphasized by the use of non-verbal language, namely the time signature 3/2, andante tempo around ♩ = 75, crescendo ( < ) and decrescendo ( > ) signs, forte ( f ), ascending and descending motion. The use of these signs emphasizes the majestic character of the hymn, which strengthens the message of deep spiritual joy and the atmosphere of worship full of appreciation.